New Threats to Human Security in the Anthropocene - United Nations Development Programme (United Nations, 2022)
New data and analysis in the report, New Threats to Human Security in the Anthropocene, shows that people’s sense of safety and security is at a low in almost every country, including the richest countries, despite years of upwards development success. Those benefiting from some of the highest levels of good health, wealth, and education outcomes are reporting even greater anxiety than 10 years ago. To tackle this disconnect between development and perceived security, the report calls for greater solidarity across borders and a new approach to development; one that allows people to live free from want, fear, anxiety and indignity. The imperative to act now has never been more clear, as new findings also show that global life expectancy at birth is falling for a second year because of COVID-19, and overall human development measures are also moving downward. Furthermore, climate change is likely to become a leading cause of death around the world. Even with moderate mitigation of emissions, some 40 million people might die because of changes in temperatures before the end of the century. The report examines a cluster of threats that have shifted to become more prominent in recent years including those from digital technologies, inequalities, conflicts, and the ability of healthcare systems to tackle new challenges like the COVID-19 pandemic. Addressing these threats will require policy makers to consider protection, empowerment, and solidarity alongside one another so that human security, planetary considerations and human development all work together and not despite each other. This means that solutions for one problem shouldn’t exacerbate other problems. The report also notes the strong association between declining levels of trust and feelings of insecurity. People with higher levels of perceived human insecurity are three times less likely to find others trustworthy.